23S rRNA assisted folding of cytoplasmic malate dehydrogenase is distinctly different from its self-folding - Sanyal, Suparna Chandra (Oxford University Press, 2002)
The role of the 50S particle of Escherichia coli ribosome and its 23S rRNA in the refolding and subunit association of dimeric porcine heart cytoplasmic malate dehydrogenase (s-MDH) has been investigated. The self-reconstitution of s-MDH is governed by two parallel pathways representing the folding of the inactive monomeric and the dimeric intermediates. However, in the presence of these folding modulators, only one first order kinetics was observed. To understand whether this involved the folding of the monomers or the dimers, subunit association of s-MDH was studied using fluorescein-5-isothiocyanate–rhodamine-isothiocyanate (FITC–RITC) fluorescence energy transfer and chemical cross-linking with gluteraldehyde. The observation suggests that during refolding the interaction of the unstructured monomers of s-MDH with these ribosomal folding modulators leads to very fast formation of structured monomers that immediately dimerise. These inactive dimers then fold to the native ones, which is the rate limiting step in 23S or 50S assisted refolding of s-MDH. Furthermore, the sequential action of the two fragments of domain V of 23S rRNA has been investigated in order to elucidate the mechanism. The central loop of domain V of 23S rRNA (RNA1) traps the monomeric intermediates, and when they are released by the upper stem–loop region of the domain V of 23S rRNA (RNA2) they are already structured enough to form dimeric intermediates which are directed towards the proper folding pathway.